Coffee-residue-based hard carbon material, preparation method thereof and application of coffee-residue-based hard carbon material in sodium battery negative electrode material
By acid-soaking and hydrothermal pretreatment of coffee grounds, a hard carbon material with a porous structure was solved, and the problems of high cost and waste of resources of existing sodium ion battery negative electrode materials are achieved, and sodium ions with high capacity and good cycle stability are achieved Battery negative electrode material.
Patent Information
- Application Number
- CN202411520630.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The existing sodium ion battery negative electrode materials are costly and difficult to produce on a large scale, and coffee grounds are not effectively utilized as waste materials, resulting in waste of resources and environmental pollution.
The coffee grounds are deeply activated through two-step pretreatment of acid leach and hydrothermal to remove impurities and retain nitrogen elements, forming a porous structure of hard carbon materials, improving their electrochemical properties.
The prepared coffee ground-based hard carbon material has excellent electrochemical properties, with a capacity of more than 179.8mAh g-1, and a capacity retention rate of more than 80.8% for 200 cycles. It is suitable for sodium ion battery negative electrode materials.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure HDA0005107951150000011
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sodium ion batteries, and in particular to a coffee grounds-based hard carbon material, a preparation method thereof, and an application thereof in sodium battery negative electrode materials. Background Art
[0002] In recent years, new energy electric vehicles and related electronic products have developed rapidly. Among them, sodium-ion batteries are regarded as the next generation of energy storage devices that are expected to replace lithium-ion batteries due to their abundant reserves, low prices, and high safety, and some companies have achieved mass production. At present, the negative electrode materials of sodium-ion batteries are mainly hard carbon materials, which can be roughly divided into fossil fuels, resins, and biomass derivatives. Fossil fuels have lower costs, but soft carbon is easy to obtain, and the gram capacity is relatively low; resin hard carbon has higher consistency and controllability, but the cost is relatively high; biomass derivatives have unique microstructures and self-doping effects, and are relatively low in cost, with prospects for large-scale production and application.
[0003] Among the many biomass-derived hard carbon materials, hard carbon materials derived from coffee grounds are receiving more and more attention. The coffee consumption market has gradually expanded in recent years. According to statistics from the Ministry of Agriculture and Rural Affairs, the global coffee production in 2022 is 10.497 million tons, of which each ton of coffee beans can produce 650 kilograms of coffee grounds, so the global annual production of coffee grounds is more than 6.8 million tons. However, most coffee grounds are discarded as domestic waste or directly incinerated, which causes resource waste and environmental pollution. However, coffee grounds are a typical three-dimensional structural material that can provide shorter channels and more pore structures, which can accelerate the migration of ions and provide more reaction sites. How to use coffee grounds, a waste material, to prepare hard carbon materials suitable for the negative electrode of sodium ion batteries, and then obtain sodium ion batteries with higher capacity and rate performance, is an urgent problem to be solved. Summary of the invention
[0004] In order to address the deficiencies of the prior art, the present invention provides a method for preparing coffee grounds-based hard carbon materials. First, the coffee grounds are subjected to a two-step pre-treatment of acid leaching and hydrothermal treatment to fully remove impurities and deeply activate the coffee grounds, while retaining the nitrogen element in the coffee grounds so that it can be doped into the porous hard carbon material structure formed by the coffee grounds during the subsequent carbonization process, thereby making the obtained hard carbon material have more abundant reaction active sites and improving the electrochemical properties of the hard carbon material.
[0005] Another object of the present invention is to provide a coffee grounds-based hard carbon material.
[0006] Another object of the present invention is to provide a negative electrode material for a sodium ion battery.
[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0008] A method for preparing a coffee grounds-based hard carbon material comprises the following steps:
[0009] S1. Acid leaching: The coffee grounds are subjected to acid leaching, wherein the acid solution used for the acid leaching is an inorganic acid with a concentration of 5 to 30 wt %, and an acid leaching product is obtained after the acid leaching;
[0010] S2. Hydrothermal treatment: The acid leaching product obtained in step S1 is mixed with an inorganic acid having a concentration of 5 to 30 wt% and subjected to a hydrothermal reaction to obtain a hard carbon precursor;
[0011] S3 carbonization: the hard carbon precursor obtained in step S2 is calcined to obtain a carbonized product;
[0012] S4. Alkali leaching: The carbonized product obtained in step S3 is subjected to alkali leaching to obtain a coffee grounds-based hard carbon material.
[0013] The preparation method of coffee grounds-based hard carbon material provided by the present invention adopts the combined method of acid leaching-hydrothermal treatment for the first time to pre-treat the coffee grounds, thereby achieving deep activation of the coffee grounds. Acid leaching can effectively remove inorganic components in the coffee grounds, and the subsequent hydrothermal treatment can further release inorganic impurities inside the coffee grounds, which helps to form a porous structure during the high-temperature carbonization process, so that the obtained hard carbon has more reactive sites, thereby improving the electrochemical properties of the material. At the same time, the combined pre-treatment method of acid leaching-hydrothermal treatment in the present invention retains the nitrogen element in the coffee grounds, so that it can be doped into the porous hard carbon material structure formed by the coffee grounds during the subsequent carbonization process, thereby making the obtained hard carbon material have more abundant reactive sites, thereby improving the electrochemical properties of the hard carbon material.
[0014] After the carbonized product is obtained by calcination in step S3, the present invention further performs alkali leaching on the carbonized product to remove silicon dioxide in the material.
[0015] It should be noted that if the concentration of the inorganic acid in steps S1 to 2 of the present invention is too low, it will affect the removal effect of inorganic impurities, and further affect the pore structure of the subsequent carbonization product; if the concentration of the inorganic acid is too high, the structure of the coffee grounds may be destroyed, resulting in the inability to obtain the expected product structure, and there is a waste of resources, which also increases the burden of post-reaction wastewater treatment.
[0016] It should be noted that in steps S1-2, it is only necessary to immerse the coffee grounds or the acid leaching product with the inorganic acid.
[0017] In a specific embodiment of the present invention, step S1 further includes the step of washing the coffee grounds before acid leaching: washing the coffee grounds until the washing liquid is colorless and transparent, and drying at 60° C. to 100° C. The purpose of washing the coffee grounds before acid leaching is to remove the scum, useless ash and water-soluble impurities on the surface of the coffee grounds.
[0018] Preferably, the inorganic acid in step S1 includes at least one of hydrofluoric acid, hydrochloric acid, nitric acid, boric acid and sulfuric acid.
[0019] In a specific embodiment of the present invention, the acid leaching in step S1 can be performed at 20°C to 60°C.
[0020] In a specific embodiment of the present invention, step S1 further comprises the steps of washing the acid leaching product with water until the washing liquid is colorless and transparent after acid leaching, and drying at 60°C to 100°C.
[0021] Preferably, the acid leaching time in step S1 is 1 to 28 days.
[0022] More preferably, the acid leaching time in step S1 is 5 to 10 days.
[0023] When the acid leaching time is 1 to 28 days, especially 5 to 10 days, the electrochemical performance of the obtained coffee grounds-based hard carbon material is better. Longer or shorter acid leaching time will lead to a decrease in the electrochemical performance of the coffee grounds-based hard carbon material. Among them, a longer acid leaching time may cause the structure of the coffee grounds to be destroyed and the electrochemical performance to decrease.
[0024] Preferably, the coffee grounds used in step S1 have a nitrogen content of 1-2%.
[0025] Coffee grounds contain about 1-2% nitrogen, mainly from inorganic components such as protein and caffeine. These inorganic components can still be retained in the structure of the coffee grounds after the acid leaching and hydrothermal pretreatment of the present invention, and are converted into nitrogen elements and doped into the hard carbon material after subsequent calcination.
[0026] Preferably, the hydrothermal temperature in step S2 is 100° C. to 200° C., and the hydrothermal time is 2 h to 12 h.
[0027] More preferably, the hydrothermal time in step S2 is 4 to 6 hours.
[0028] In a specific embodiment of the present invention, after the hydrothermal reaction in step S2 is completed, the steps of washing the product until the washing liquid is colorless and transparent and drying are also included.
[0029] Preferably, the calcination in step S3 is performed in an inert atmosphere. Specifically, the inert atmosphere may be nitrogen or argon.
[0030] In a specific embodiment of the present invention, the calcination temperature in step S3 may be 600-2000° C., and the heating rate may be 2-10° C. / min.
[0031] Preferably, the calcination temperature in step S3 is 800-1700°C.
[0032] More preferably, the calcination temperature in step S3 is 1000-1400°C.
[0033] Preferably, the calcination time in step S3 is 2 to 15 hours.
[0034] More preferably, the calcination time in step S3 is 6 to 12 hours.
[0035] The temperature and time of calcination will affect the degree of graphitization of coffee grounds-based hard carbon materials. The calcination time and temperature are controlled to ensure that the coffee grounds form hard carbon while avoiding the appearance of graphitized carbon. When the calcination temperature is increased to 800-1700°C and the calcination time is 2-15h, especially when the calcination temperature reaches 1000-1400°C and the calcination time is 6-12h, the resulting hard carbon material has better electrochemical properties. However, when the calcination temperature is higher and the time is too long, it may lead to the appearance of graphitized carbon, affecting the performance of the hard carbon material.
[0036] Preferably, the alkali solution used in the alkali leaching in step S4 is an inorganic alkali solution with a concentration of 0.1 to 1 mol / L, and the inorganic alkali includes at least one of sodium hydroxide, sodium carbonate and sodium bicarbonate.
[0037] In a specific embodiment of the present invention, the temperature of the alkali leaching in step S4 may be 20-60°C.
[0038] Preferably, the temperature of the alkali leaching in step S4 is 35-60°C.
[0039] Preferably, the alkali leaching time in step S4 is 9 to 24 hours.
[0040] In a specific embodiment of the present invention, after the alkali leaching in step S4, the step of washing and drying the product is also included.
[0041] In a specific embodiment of the present invention, the N content of the coffee grounds-based hard carbon material obtained in step S4 is 1-3%.
[0042] The present invention also protects a coffee grounds-based hard carbon material prepared by the method for preparing the coffee grounds-based hard carbon material.
[0043] The present invention also protects a sodium ion battery negative electrode material, comprising the coffee grounds-based hard carbon material.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] The coffee grounds-based hard carbon material is prepared by the method provided by the present invention, which can fully remove impurities and deeply activate the coffee grounds, and dope the nitrogen element in the raw coffee grounds into the hard carbon material structure formed subsequently. Therefore, the obtained material has excellent electrochemical properties, and the capacity can reach 179.8 mAh g when applied to sodium battery. -1 The capacity retention rate after 200 cycles can reach more than 80.8%. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 The present invention provides a flow chart of a method for preparing a coffee grounds-based hard carbon material.
[0047] Figure 2 This is the XRD pattern of the coffee grounds-based hard carbon material prepared in Example 2 of the present invention.
[0048] Figure 3 This is a SEM image of the coffee grounds-based hard carbon material prepared in Example 2 of the present invention.
[0049] Figure 4 This is the XPS graph of the coffee grounds-based hard carbon material prepared in Example 2 of the present invention.
[0050] Figure 5 The coffee grounds-based hard carbon material prepared in Example 2 of the present invention was heated to a current density of 0.1 A·g -1 The charge and discharge curves for 20 cycles.
[0051] Figure 6 This is a rate performance test diagram of the coffee grounds-based hard carbon material prepared in Examples 1 to 8 of the present invention.
[0052] Figure 7 This is a rate performance test diagram of the coffee grounds-based hard carbon material prepared in Comparative Examples 1 to 7 of the present invention. DETAILED DESCRIPTION
[0053] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents. Among them, the raw material information used in each embodiment and comparative example is as follows:
[0054] Coffee grounds: provided by Changzhou Kangruize Supply Chain Management Co., Ltd.
[0055] Example 1
[0056] A method for preparing a coffee grounds-based hard carbon material comprises the following steps:
[0057] S1. Acid leaching: Wash coffee grounds with a nitrogen content of 1-2% with water until the washing liquid is colorless and transparent, dry at 80°C, and then acid-leach the coffee grounds. The acid used for the acid leaching is a hydrochloric acid solution with a concentration of 10wt%, the acid leaching temperature is 25°C, the time is 7d, and the acid leaching product is obtained after the acid leaching, washed with water until the washing liquid is colorless and transparent, and dried at 80°C;
[0058] S2. Hydrothermal treatment: The acid leaching product obtained in step S1 is mixed with a 10 wt% hydrochloric acid solution so that the hydrochloric acid solution can immerse the acid leaching product, and the reaction is performed at 150 ° C for 6 hours. After the reaction, the product is washed until the washing liquid is colorless and transparent, and dried to obtain a hard carbon precursor;
[0059] S3 carbonization: the hard carbon precursor obtained in step S2 was calcined at a heating rate of 5 ° C / min to 900 ° C in an argon atmosphere for 2h to obtain a carbonized product after calcination;
[0060] S4. Alkali leaching: The carbonized product obtained in step S3 is immersed in a 0.5 mol / L sodium hydroxide solution at 40°C for 12 hours, and then washed and dried to obtain a coffee grounds-based hard carbon material with a nitrogen content of 2%.
[0061] Example 2
[0062] A method for preparing a coffee grounds-based hard carbon material, which differs from Example 1 only in that:
[0063] The calcination temperature in step S3 is 1300°C.
[0064] Example 3
[0065] A method for preparing a coffee grounds-based hard carbon material, which differs from Example 1 only in that:
[0066] The calcination temperature in step S3 is 1700°C.
[0067] Example 4
[0068] A method for preparing a coffee grounds-based hard carbon material, which differs from Example 1 only in that:
[0069] In step S3, the calcination temperature is 1100° C. and the calcination time is 6 hours.
[0070] Example 5
[0071] A method for preparing a coffee grounds-based hard carbon material, which differs from Example 1 only in that:
[0072] In step S3, the calcination temperature is 1100° C. and the calcination time is 12 h.
[0073] Example 6
[0074] A method for preparing a coffee grounds-based hard carbon material, which differs from Example 2 only in that:
[0075] The acid leaching time in step S1 is 14 days.
[0076] Example 7
[0077] A method for preparing a coffee grounds-based hard carbon material, which differs from Example 2 only in that:
[0078] The acid leaching time in step S1 is 1 day.
[0079] Example 8
[0080] A method for preparing a coffee grounds-based hard carbon material, which differs from Example 2 only in that:
[0081] The hydrothermal time in step S2 is 12 h.
[0082] Comparative Example 1
[0083] A method for preparing a coffee grounds-based hard carbon material comprises the following steps:
[0084] S1. Carbonization: Wash the coffee grounds with water until the washing liquid is colorless and transparent, dry them, and then calcine the coffee grounds in an argon atmosphere at a heating rate of 5°C / min to 1300°C for 2 hours to obtain a carbonized product;
[0085] S2. Alkali leaching: The carbonized product obtained in step S1 is immersed in a 0.5 mol / L sodium hydroxide solution at 40°C for 12 hours, and then washed and dried to obtain a coffee grounds-based hard carbon material.
[0086] Comparative Example 2
[0087] A method for preparing a coffee grounds-based hard carbon material comprises the following steps:
[0088] S1. Acid leaching: Wash the coffee grounds with water until the washing liquid is colorless and transparent, and then dry the coffee grounds and perform acid leaching, wherein the acid solution used for the acid leaching is a 10wt% hydrochloric acid solution, the acid leaching temperature is 25°C, the time is 7d, and the acid leaching product is obtained after the acid leaching, and washed with water until the washing liquid is colorless and transparent, and then dried;
[0089] S2. Carbonization: The acid leaching product obtained in step S1 was calcined at a heating rate of 5°C / min to 1300°C in an argon atmosphere for 2h to obtain a carbonized product after calcination;
[0090] S3. Alkali leaching: The carbonized product obtained in step S2 is immersed in a 0.5 mol / L sodium hydroxide solution at 40°C for 12 hours, and then washed and dried to obtain a coffee grounds-based hard carbon material.
[0091] Comparative Example 3
[0092] A method for preparing a coffee grounds-based hard carbon material comprises the following steps:
[0093] S1. Hydrothermal treatment: Wash the coffee grounds with water until the washing liquid is colorless and transparent, dry the coffee grounds and mix them with a 10 wt% hydrochloric acid solution, and perform a hydrothermal reaction at 150°C for 6 hours. After the reaction, wash the product until the washing liquid is colorless and transparent, and dry it to obtain a hard carbon precursor;
[0094] S2. Carbonization: The acid leaching product obtained in step S1 was calcined at a heating rate of 5°C / min to 1300°C in an argon atmosphere for 2h to obtain a carbonized product after calcination;
[0095] S3. Alkali leaching: The carbonized product obtained in step S2 is immersed in a 0.5 mol / L sodium hydroxide solution at 40°C for 12 hours, and then washed and dried to obtain a coffee grounds-based hard carbon material.
[0096] Comparative Example 4
[0097] A method for preparing a coffee grounds-based hard carbon material comprises the following steps:
[0098] S1. Acid leaching: Wash the coffee grounds with water until the washing liquid is colorless and transparent, and then dry the coffee grounds and perform acid leaching. The acid solution used for the acid leaching is a hydrochloric acid solution with a concentration of 10wt%, the acid leaching temperature is 25°C, the time is 14d, and the acid leaching product is obtained after the acid leaching, and washed with water until the washing liquid is colorless and transparent, and then dried;
[0099] S2. Alkali leaching: The acid leaching product obtained in step S1 is immersed in a 0.5 mol / L sodium hydroxide solution at 40°C for 12 hours, and then washed and dried to obtain an alkali leaching product;
[0100] S3. Hydrothermal treatment: The alkali leaching product obtained in step S2 was mixed with a 10wt% hydrochloric acid solution, and the reaction was hydrothermally reacted at 150°C for 6h. After the reaction, the product was washed until the washing liquid was colorless and transparent, and dried to obtain a hard carbon precursor;
[0101] S4. Carbonization: calcine the hard carbon precursor obtained in step S3 at a heating rate of 5°C / min to 1300°C in an argon atmosphere for 2 hours to obtain a coffee grounds-based hard carbon material.
[0102] Comparative Example 5
[0103] A method for preparing a coffee grounds-based hard carbon material comprises the following steps:
[0104] S1. Alkali leaching: Wash the coffee grounds with water until the washing liquid is colorless and transparent, and then dry the coffee grounds and soak them in a 0.5 mol / L sodium hydroxide solution at 40°C for 12 hours to obtain an alkali leached product, wash it with water until the washing liquid is colorless and transparent, and dry it;
[0105] S2. Hydrothermal treatment: The alkali leaching product obtained in step S1 was mixed with a 10wt% hydrochloric acid solution, and the mixture was hydrothermally reacted at 150°C for 6h. After the reaction, the product was washed until the washing liquid was colorless and transparent, and dried to obtain a hard carbon precursor;
[0106] S3 carbonization: in an argon atmosphere at a heating rate of 5 ° C / min to 1300 ° C the hard carbon precursor obtained in step S2 was calcined for 2h to obtain a carbonized product after calcination;
[0107] Comparative Example 6
[0108] A method for preparing a corncob powder-based hard carbon material, which differs from Example 2 only in that:
[0109] The raw coffee grounds in step S1 are replaced with corn cob powder.
[0110] Comparative Example 7
[0111] A method for preparing a coffee grounds-based hard carbon material, which differs from Example 2 only in that:
[0112] In step S2, the acid leaching product and deionized water are subjected to a hydrothermal reaction.
[0113] Performance Testing
[0114] Electrochemical performance test: The hard carbon material prepared in the embodiment and the comparative example is dispersed in a solvent N-methylpyrrolidone with a mass ratio of 8:1:1, and the slurry is coated on a copper foil. After drying, it is cut into 12 mm discs for further assembly of button batteries. CR2025 button batteries are assembled in a high-purity argon atmosphere (water and oxygen content are both less than 10 ppm). The negative electrode is the hard carbon material disc prepared above, the counter electrode is a metal sodium sheet, the diaphragm is Whatman glass fiber, and the electrolyte is a solution obtained by dissolving 1M sodium perchlorate in a mixed solvent of ethylene carbonate and diethyl carbonate (volume ratio of 1:1). After the battery is sealed and left to stand at room temperature for 8 hours, electrochemical testing can be carried out.
[0115] The performance test data is shown in Table 1. Figures 2 to 7 As shown:
[0116] Table 1. Capacity-related data of hard carbon materials obtained in Examples and Comparative Examples
[0117]
[0118]
[0119] As shown in Table 1 above, the coffee grounds-based hard carbon material prepared by the method provided by the present invention has excellent electrochemical properties, and the capacity can reach 161.7 mAh g when applied to sodium battery. -1 Above, the capacity retention rate after 200 cycles can also reach more than 76.3%. Among them, according to the data of Examples 1 to 5, it can be seen that when the calcination time increases from 900°C (Example 1) to 1300°C (Example 2), and then to 1700°C (Example 3), the capacity first increases and then decreases, indicating that too high a calcination temperature will also cause the performance of the hard carbon material to decrease. Therefore, the present invention further prefers that the calcination temperature is 1000-1400°C. When the calcination time is increased from 2h (Example 1) to 6h (Example 4) and then to 12h (Example 5), the capacity of the obtained hard carbon material is improved to a certain extent, but the capacity retention rate does not show a significant difference. Considering the energy consumption and the degree of improvement, it is further preferred that the calcination time is 6-12h.
[0120] According to the data of Examples 1 and 6-7, it can be seen that when the acid leaching time is 7 days (Example 1), the capacity and cycle capacity retention rate of the coffee residue-based hard carbon material are significantly better than those of the hard carbon material obtained by acid leaching for 1 day (Example 7); when the acid leaching time is further increased to 14 days (Example 6), the electrochemical performance of the obtained hard carbon material decreases again, and it is speculated that too long acid leaching time may cause the coffee residue-based structure to be destroyed. Based on this, the present invention further prefers that the acid leaching time is 5-10 days.
[0121] According to the data of Examples 1 and 8, it can be seen that when the time of the hydrothermal reaction in step S2 is increased from 6 h (Example 1) to 12 h (Example 8), the electrochemical properties of the hard carbon material are not significantly improved, but the energy consumption is significantly improved. Therefore, the present invention further prefers that the hydrothermal time is 4 to 6 h.
[0122] According to the data of Comparative Examples 1 to 5, it can be seen that the selection of process steps and their order in the method provided by the present invention are extremely critical. Comparative Examples 1 to 3 are schemes in which the acid leaching-hydrothermal pretreatment steps lack one step or are not pretreated, respectively. The electrochemical capacity of the hard carbon materials obtained is significantly inferior to that of the embodiment, indicating the performance superiority of the hard carbon obtained by the two-step pretreatment method, reflecting the advantage of the idea of deep activation. The data of Comparative Examples 4 to 5 show that adjusting the order of acid leaching, hydrothermal, calcination, and alkali washing treatment methods will also affect the performance of the material. For example, in Comparative Example 4, according to the treatment sequence of acid leaching, alkali washing, hydrothermal and calcination, its performance is significantly lower than that of Example 2. The performance of the material obtained by the alkali washing, hydrothermal and calcination treatment method in Comparative Example 5 is lower than that of Example 2 and Comparative Example 4, indicating the importance of acid leaching, and the acid leaching step in the two-stage pretreatment cannot be replaced by alkali washing. At the same time, the treatment method in Comparative Example 6 is the same as that in Example 2, but the raw material is changed to corn cobs. Its rate performance is not only far lower than that of Example 2, but also has no advantage compared with Comparative Examples 1 to 3, indicating the criticality of raw material selection. In addition, the hydrothermal reaction medium in Example 2 was changed to pure water (Comparative Example 7), and its performance was inferior to that of Example 2, which shows the importance of the selection of hydrothermal reaction medium.
[0123] Figure 2 This is the XRD pattern of the coffee grounds-based hard carbon material prepared in Example 2 of the present invention. Figure 2 As shown, the broad peaks at 22° and 43° correspond to the (002) and (100) crystal planes of hard carbon, indicating that hard carbon material can be obtained by the preparation method of the present invention.
[0124] Figure 3 This is a SEM image of the coffee grounds-based hard carbon material prepared in Example 2 of the present invention. Figure 3 This SEM image confirms that the hard carbon material prepared in the present invention has a porous structure.
[0125] Figure 4 This is the XPS graph of the coffee grounds-based hard carbon material prepared in Example 2 of the present invention. Figure 4 It can be seen that the main elements in the hard carbon material prepared by the present invention are C, N, and O, among which the content of N is relatively small, which is contained in the coffee grounds raw material and is still retained after a series of treatments.
[0126] Figure 5 The coffee grounds-based hard carbon material prepared in Example 2 of the present invention was heated to a current density of 0.1 A·g -1 From the charge and discharge curve diagram when the cycle is 20, it can be known that the hard carbon material of the present invention has a long voltage platform at about 0.1V. This phenomenon is the characteristic data of hard carbon. It can also be confirmed that the material prepared by the present invention is a hard carbon material.
[0127] Figure 6This is a rate performance test diagram of coffee grounds-based hard carbon materials prepared in Examples 1 to 7 and Comparative Example 8 of the present invention. Figure 7 This is a rate performance test diagram of coffee grounds-based hard carbon materials prepared in Comparative Examples 1 to 7 of the present invention. Figure 6 and Figure 7 It can be seen that by using the method provided in the embodiment of the present invention to prepare coffee grounds-based hard carbon material, the rate performance of the obtained material is significantly improved.
[0128] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a coffee grounds-based hard carbon material, characterized in that: The steps include: S1. Acid leaching: The coffee grounds are subjected to acid leaching, wherein the acid solution used for the acid leaching is an inorganic acid with a concentration of 5 to 30 wt %, and an acid leaching product is obtained after the acid leaching; S2. Hydrothermal treatment: The acid leaching product obtained in step S1 is mixed with an inorganic acid having a concentration of 5 to 30 wt% and subjected to a hydrothermal reaction to obtain a hard carbon precursor; S3 carbonization: the hard carbon precursor obtained in step S2 is calcined to obtain a carbonized product; S4. Alkali leaching: The carbonized product obtained in step S3 is subjected to alkali leaching to obtain a coffee grounds-based hard carbon material.
2. The method for preparing coffee grounds-based hard carbon material according to claim 1, characterized in that: The inorganic acid in step S1 includes at least one of hydrofluoric acid, hydrochloric acid, nitric acid, boric acid and sulfuric acid.
3. The method for preparing coffee grounds-based hard carbon material according to claim 1, characterized in that: The acid leaching time in step S1 is 1 to 28 days.
4. The method for preparing coffee grounds-based hard carbon material according to claim 1, characterized in that: The nitrogen content of the coffee grounds used in step S1 is 1-2%.
5. The method for preparing coffee grounds-based hard carbon material according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step S2 is 100° C. to 200° C., and the time is 2 h to 12 h.
6. The method for preparing coffee grounds-based hard carbon material according to claim 1, characterized in that: The calcination in step S3 is carried out in an inert atmosphere, the calcination temperature is 800-1700° C., and the time is 2-15 hours.
7. The method for preparing coffee grounds-based hard carbon material according to claim 1, characterized in that: The alkali solution used in the alkali leaching in step S4 is an inorganic alkali solution with a concentration of 0.1 to 1 mol / L, and the inorganic alkali includes at least one of sodium hydroxide, sodium carbonate, and sodium bicarbonate.
8. The method for preparing coffee grounds-based hard carbon material according to claim 1, characterized in that: The temperature of the alkali leaching in step S4 is 35-60°C.
9. A coffee grounds-based hard carbon material prepared by the method for preparing a coffee grounds-based hard carbon material according to any one of claims 1 to 8.
10. A negative electrode material for a sodium ion battery, characterized in that: The method comprises the coffee grounds-based hard carbon material as claimed in claim 9.
Citation Information
Patent Citations
Hard carbon negative electrode material, manufacturing method thereof, and method for manufacturing battery using the hard carbon negative electrode material
CN109256561A
Preparation process of sulfur-doped biomass porous carbon nanoelectrode material for long-cycle lithium-ion battery
CN110299537A
Biomass hard carbon as well as preparation method and application thereof
CN116986581A
Treatment method of kitchen waste biogas residues, endogenous calcium-doped porous biochar and application of endogenous calcium-doped porous biochar
CN117105209A
Defective MnO doped charcoal modified red mud catalyst as well as preparation method and application thereof
CN117861680A